Dinamika Pelaksanaan Program Asistensi Mengajar: Studi Kasus Pembelajaran IPS di Kelas IX MTs Hizbul Wathan NWDI Semaya - Huldiya Syamsiar; Dina Rosa Kusumayanti; Maulida Melianti; Muhammad Khairul Iman (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
The study aims to analyze the dynamics of the teaching assistance program in the context of Social Studies (IPS) learning in grade IX at MTs Hizbul Wathan NWDI Semaya. This study uses a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving teachers, students, and students participating in the assistance program. The results of the study show that the teaching assistance program has a positive impact on improving the quality of social studies learning, particularly in terms of student participation, variety of teaching techniques, and the development of students' reflective abilities. Students function as learning facilitators who contribute to creating an interactive and collaborative classroom environment, while teachers act as professional mentors who ensure that the learning process follows the established curriculum.